Expanding the clinical phenotype of the ultra-rare Skraban-Deardorff syndrome: Two novel individuals with WDR26 loss-of-function variants and a literature review - Pavinato, Lisa; Trajkova, Slavica; Grosso, Enrico; Giorgio, Elisa; Bruselles, Alessandro; Radio, Francesca Clementina; Pippucci, Tommaso; Dimartino, Paola; Tartaglia, Marco; Petlichkovski, Aleksandar; De Rubeis, Silvia; Buxbaum, Joseph; et al. (Wiley, 2021)
De novo variants in the WDR26 gene leading to haploinsufficiency have recently been associated with Skraban-Deardorff syndrome. This condition is an ultra-rare autosomal dominant neurodevelopmental disorder characterized by a broad range of clinical signs, including intellectual disability (ID), developmental delay (DD), seizures, abnormal facial features, feeding difficulties, and minor skeletal anomalies. Currently, 18 cases have been reported in the literature and for only 15 of them a clinical description is available. Here, we describe a child with Skraban-Deardorff syndrome associated with the WDR26 pathogenic de novo variant NM_025160.6:c.69dupC, p.(Gly24ArgfsTer48), and an adult associated with the pathogenic de novo variant c.1076G > A, p.(Trp359Ter). The adult patient was a 29-year-old female with detailed information on clinical history and pharmacological treatments since birth, providing an opportunity to map disease progression and patient management. By comparing our cases with published reports of Skraban-Deardorff syndrome, we provide a genetic and clinical summary of this ultrarare condition, describe the clinical management from childhood to adult age, and further expand on the clinical phenotype.